Ceramics and composites preparation and applications - Burduhos-Nergis, D. D. (Materials research foundations ;, 2022)
"The book presents a state-of-the-art survey of ceramics and composites. It focuses on the flexible and efficient manufacture of objects with specific shapes, complexity and tailor-made characteristics and properties. Keywords: Metal Matrix Composites, Polymer Matrix Composites, Ceramic Composite Materials, Composite Manufacturing Methods, Compressive Pouring, Vacuum Bagging, Filament Winding, Centrifugal Casting, Pultrusion, Automatic Fiber Positioning, Automatic Laying, Tape, Aeronautical Applications, Missile Aerospace Systems, Marine Applications, Prevention of Earthquake Damage, Machine Construction, Rubber Laminates, Flexible Gaskets."--